Translingual English, Facebook, and gay identities - Dovchin, Sender (2020)
This paper discusses the role of English in ‘enacting one's sexuality’ or ‘gendered identities’ in the Facebook practices of gay Mongolian men. Drawing on digital ethnographic studies, the study aims to illustrate how the role of English needs to be understood from the sophisticated complexities of ‘translingual English’ authored by Facebook users. It presents how Mongolian Facebook users are frequently involved with translingual English practices through their extensive relocalization of variable resources, including English, Mongolian, and other forms of codes, modes, styles, repertoires, and genres. The study also demonstrates how translingual English users deploy Facebook as a highly potent site and formula for the construction and performance of their ‘sexuality.’.